Modern weapons and military equipment for issue 1-2020 - Vučković, Dragan M. (Vojnotehnički glasnik / Military Technical Courier, 2020)
Turkey uses laser weapon technology to shoot down Chinese UAV Wing Loong II in Libya; Forget Stealth Fighters: Is This Russia's Deadliest Warplane of All?;Russia Keeps Losing Its T-90 Tanks in Syria for One Reason; France’s First “Barracuda” Attack Submarine Has Taken to the Water (And Is Quieter & Deadlier Than Ever); Meet the Qing-Class: China's Homegrown Nuclear Missile Submarine.